Entrepreneurship and tourism investment projects in the desert, according to social norms of governance - ابريعم سامية (Finance and Business Economies Review, 2023)
The investment projects of the construction enterprises are one of the most important pillars of development in the economic and social field. They contribute significantly to the construction of infrastructure through the construction of roads and the construction of residential and service structures such as hotels ... as well as the employment of individuals in various activities, which means providing income for these and thus reducing unemployment Relatively speaking, the Algerian Sahara is considered a tourist area with excellence due to its natural and cultural attractions. However, it has not received sufficient attention in the field of tourism investment by the contracting institutions and suffers from the weakness of the social responsibility obligations Which allows them to enjoy projects that contribute to their formation and growth in accordance with international standards of governance and sustainable development. Therefore, this intervention comes in order to present the challenges and requirements of the investment promotion of the South tourist areas.